Fibre optic interconnecting devices and passive components. Performance standard. Non-connectorized single-mode fibre optic LAN WDM devices with channel spacing of 800 GHz for category C. Controlled environments Part 088-2, (31st July 2013) - British Standards Institution,
No abstract available